Biogeography of the Jaera albifrons superspecies (Isopoda, Asellota) on the Atlantic coast of Canada - Veuille, Michel (Canadian Journal of Zoology, 1976)
The biogeographical study of the four Canadian forms of the Jaera albifrons superspecies leads to a division into two groups. J. (a.) albifrons, J. (a.) ischiosetosa, and J. (a.) praehirsuta are spread along the whole Atlantic coast, from cold to temperate shores but, as in Europe, salinity and exposure affect their relative abundance. J. (a.) posthirsuta occurs only in the warm shallow waters protected from arctic currents. The presumably postglacial origin of its disjunct distribution is discussed.